The eclipse of the demos : the Cold War and the crisis of democracy before neoliberalism - Son, Kyong-Min (Book collections on Project MUSE., 2020)
"The twenty-first century has seen a global erosion in the institutions of democracy. Support for democracy is waning in new democracies, while in Europe and the United States trust and civic participation are declining. Many today are asking whether democracy can be saved, and leading scholars speak of a "crisis of democracy." Much of the current literature places the blame for this situation on the rise of neoliberalism and the dissolution of the welfare state, but Kyong-Min Son argues that the debate over this crisis could benefit from a longer historical perspective, particularly from a close look at the development of democratic theory in the post-World War II era. Under the pressure of the Cold War, the social and institutional arrangements that we identify as democracy today took shape. Built into this arrangement from the start was a fear of "the masses" as a mortal threat to democracy, and this fear led to the construction of an instrumentalized form of democracy whose purpose was found in advancing individuals' private interests rather than in forming a democratic people as a public, communal institution. The transformation of democracy during the Cold War encounter with totalitarianism and communism linked it closely to free-market capitalism, preparing the way for democracy's further deterioration in the 1970s under the influence of neoliberalism. The result was a demos indifferent to anything beyond the individual's immediate interests. Drawing on the work of Hannah Arendt, The Eclipse of the Demos theorizes an alternative account of the demos defined by attunement to the voices of suffering and disenfranchisement that characterize democratic life"--